2018
DOI: 10.1038/s41598-018-22607-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antibiotics and NSAIDs on cyclooxygenase-2 in the enamel mineralization

Abstract: The objective of this study was to determine whether the use of the most commonly prescribed antibiotics and non-steroidal anti-inflammatory drugs in childhood could disturb enamel mineralization. Forty-two Swiss mice were divided into seven groups: controls; amoxicillin; amoxicillin/clavulanate; erythromycin; acetaminophen; ibuprofen and celecoxib, to inhibit cyclooxygenase 2 (COX2). SEM-EDX analysis was conducted on all cusps of the third molars. Calcium (Ca), phosphorus (P), aluminum, potassium, sodium, mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 32 publications
0
13
1
Order By: Relevance
“…Childhood infections can disturb ameloblasts during the late secretory or early maturation stage either directly or indirectly through malnutrition, an increase in temperature, pH shifts, hypoxia, or hypocalcemia. 35 39 Children with a breastfeeding history of >18 months presented with 3.73 times greater MIH risk. Prolonged breastfeeding may increase exposure to dioxins, which are widely spread environmental pollutants.…”
Section: Discussionmentioning
confidence: 99%
“…Childhood infections can disturb ameloblasts during the late secretory or early maturation stage either directly or indirectly through malnutrition, an increase in temperature, pH shifts, hypoxia, or hypocalcemia. 35 39 Children with a breastfeeding history of >18 months presented with 3.73 times greater MIH risk. Prolonged breastfeeding may increase exposure to dioxins, which are widely spread environmental pollutants.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that COX-2 was involved in enamel maturation and the inhibition of COX-2 could inhibit the formation of tooth enamel. 28 PGE2 also affected the maturation of mineralization. 29 The inhibitory effect of meloxicam on COX-2 and the regulation of PGE2 may be related to the maturation of odontogenic mineralization, which requires further investigation.…”
Section: Discussionmentioning
confidence: 96%
“…Ameloblasts are able to deposit the enamel matrix, but due to the low oxygen demand they have difficulties reabsorbing the proteins from the matrix, compromising the calcium phosphate deposit. This lack of oxygen can occur due to complications in childbirth, respiratory problems, renal problems that characterize an inadequate supply of calcium phosphate, diarrhea, malnutrition, and frequent childhood diseases with a history of high fever 6,10,11,14,16 .…”
Section: Discussionmentioning
confidence: 99%
“…According to some studies, patients with respiratory diseases such as asthma, bronchitis and allergic rhinitis are more likely to develop enamel defects 1,8,9 . Enamel matrix is affected due to low oxygen demand, inhibiting the action of proteolytic enzymes compromising the formation of hydroxyapatite crystal, resulting in hypo mineralized enamel 1,11 .…”
Section: Introductionmentioning
confidence: 99%